(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Acute on the face, jaw and neck (abscess, phlegmon, osteomyelitis, purulent inflammatory diseases to surrounding tissues organ necessary for life as a result of spread, poisoning of the body and .This article describes the historical formation of the field of facial and jaw surgery and today provides information about its state of modernization. Also In the article, common diseases in this field and their treatment practice thoughts about.